Efeito da re-nitretação nas propriedades de matrizes de extrusão a quente de alumínio, confeccionadas em aços ferramenta vex e h13 - Ottani, Vinicius Cardoso (Universidade Federal de São Carlos, 2018)
Aluminum extrusion is a thermomechanical process widely used throughout the world, and the performance of this process is strongly dependent on the quality of the tool steel used in the manufacture of the dies. In this context, the present study aimed to evaluate and compare the mechanical and microstructural properties of AISI H13 and VEX hot work tool steels, the effect of re-nitriding on die recovery and tooling performance in field tests. The samples were nitrided with gas and plasma for comparison purposes. The effect of re-nitriding was simulated by performing eleven consecutive nitriding cycles on the samples. The samples were characterized by chemical analysis, metallography, X-ray diffraction, SEM-EDS, hardness tests, impact tests and machinability tests. The tubular dies made of both materials were used in the extrusion of AA6060 aluminum alloy profiles for performance evaluation. The results showed that the increase in the number of nitriding cycles influences the surface nitrogen concentration, the white layer and the diffusion zone thickness, the surface oxides growth, the nitrided layer hardness and the substrate hardness. The residual stress profiles of the nitride layer and the effect of the alloying elements on the temperability of both materials were also compared. The experimental simulation of the effect of the working temperature on the dies proved the superior performance of VEX when compared to H13. The higher wear resistance of VEX was attributed to higher resistance to the tempering of the nitride layer and the substrate and depth of the nitride layer after the same number of nitriding cycles.
Effect of re-nitriding on the properties of hot extrusion dies of alluminum made of tool steels vex and h13
Keywords: Nitretação; Aço ferramenta; Extrusão; Nitriding; Tool steel; Extrusion; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA